Seismostratigraphy of the Eastern Lomonosov Ridge and Adjacent Amundsen Basin - Weigelt, Estella; Jokat, Wilfried (2017)
The contribution presents high-resolution seismic reflection profiles collected along and across the Lomonosov Ridge with a focus on its Eurasian side. The seismic lines provide images on the structure of sedimentary sequences and the surface of the acoustic basement. We will describe our findings in special view to appropriate drill site locations proposed for the upcoming IODP-708 project (ACEX II). All profiles show similar reflection characteristics for the upper sedimentary succession corresponding to seismic records of other regions of the Arctic Ocean. This enabled a classification into seismic units and the assignment of ages after present seismostratigraphic models. A tie point for dating is a pronounced high-amplitude reflectors sequence (HARS), which is the most striking feature in the Siberian part of the Arctic Ocean. The top of the reflector band is suggested to mark the end of Oligocene, and its base likely corresponds to the base of Eocene (56 Ma). The intervall velocities in this HARS show only minor changes or even decrease compared to the seismic units above which we associate with the presence of black shales. The HARS indicates strong and widespread changes in deposition conditions associated with reorientation of Arctic Plates, accompanied by gradual opening of the Fram Strait, and widespread regression of sea level. The top of HARS seems to present a gliding plane as indicated by mass wasting structures in the sequences above. Another marked seismic unit, as well striking by high-amplidue reflectors, parallels the seafloor with a constant thickness of about 160 m. Likely it marks the large-scale glaciation of the northern hemisphere, and its widespread impact on the deposition environment of the ridge and adjacent basins. A pronounced BSR as desribed in earlier studies turned out to be an artefact resulting from a bubble signal. Towards the Amundsen Basin the slope of the Ridge is structured into three faulted crustal blocks indicating large scale vertical motions which we associate with ...